2017
DOI: 10.1920/wp.cem.2017.4217
|View full text |Cite
|
Sign up to set email alerts
|

Fixed effect estimation of large T panel data models

Abstract: This article reviews recent advances in fixed effect estimation of panel data models for long panels, where the number of time periods is relatively large. We focus on semiparametric models with unobserved individual and time effects, where the distribution of the outcome variable conditional on covariates and unobserved effects is specified parametrically, while the distribution of the unobserved effects is left unrestricted. Compared to existing reviews on long panels (Arellano & Hahn, 2007; a section in Are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…In the mineral systems, F7 and F14 are pointing in different directions. This is consistent with chemical shift data, relaxation dynamics (T 1 /T 1ρ ) 20,27 , 13 C{ 31 P} REDOR 20 , 2 H ssNMR 27 , and NEXAFS 24 data, which all conclude that F7 is far from the HAP surface (at least 7 Å) while F14 is close to (within 4 Å) and interacting with the surface. The ΔCS values in this study support this theory, since there are significant perturbations for F14 ( 13 Cγ, 13 Cδ, 13 Cε, and 13 Cζ data), yet much smaller perturbations for the same shifts of F7.…”
Section: Sna15 Secondary Structure Predictions From Talos-nsupporting
confidence: 79%
See 4 more Smart Citations
“…In the mineral systems, F7 and F14 are pointing in different directions. This is consistent with chemical shift data, relaxation dynamics (T 1 /T 1ρ ) 20,27 , 13 C{ 31 P} REDOR 20 , 2 H ssNMR 27 , and NEXAFS 24 data, which all conclude that F7 is far from the HAP surface (at least 7 Å) while F14 is close to (within 4 Å) and interacting with the surface. The ΔCS values in this study support this theory, since there are significant perturbations for F14 ( 13 Cγ, 13 Cδ, 13 Cε, and 13 Cζ data), yet much smaller perturbations for the same shifts of F7.…”
Section: Sna15 Secondary Structure Predictions From Talos-nsupporting
confidence: 79%
“…The role of phenylalanine residues in the binding of statherin to HAP has been studied extensively. 20,24,27 Gibson and coworkers 20 studied the role of F7 and F14 in SN15 adsorption to HAP through isotropic chemical shift perturbations, 13 C{ 31 P} REDOR, and T 1ρ relaxation measurements. They found that when compared to F7, F14 is closer to the surface and is more dynamically constrained.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations